Unsteady Squeezing Flow and Heat Transfer Analysis of Magnetohydrodynamic Third-grade Nanofluid between Two Disks Embedded in a Porous Medium subjected to Thermal Radiation using Homotopy Perturbation Method - Gbeminiyi Musibau Sobamowo; Ahmed Amoo Yinusa; Mufutau Adekojo Waheed; Antonio Marcos de Oliveira Siqueira (The Journal of Engineering and Exact Sciences)
The non-linear behaviours of non-Newtonian fluids under various flow conditions continue to arouse research interests in recent times. In this work, nonlinear analysis of unsteady squeezing flow and heat transfer of a third-grade nanofluid between two parallel disks embedded in a porous medium under the influences of thermal radiation and temperature jump boundary conditions is studied using homotopy perturbation method. The parametric studies from the series solutions show that for a suction parameter greater than zero, the lower disc's radial velocity increases while that of the upper disc decreases as a result of a corresponding increase in the viscosity of the fluid from the lower squeezing disc to the upper disc. An increasing magnetic field parameter and the radial velocity of the lower disc decrease while that of the upper disc increases. There is a recorded decrease in the fluid temperature profile as the Prandtl number increases due to a decrease in the third-grade fluid's thermal diffusivity. The results of this work can be used to advance the analysis and study of third-grade nanofluid flow behavior and heat transfer processes.